2016
DOI: 10.1111/raq.12183
|View full text |Cite
|
Sign up to set email alerts
|

A revisit to fishmeal usage and associated consequences in Chinese aquaculture

Abstract: China has dominated global aquaculture production for more than two decades. Aquaculture production in China increased from 24.6 million metric tons (mmt) in 2000 to 47.5 mmt in 2014, an increment of 93.1%. Along with the fast‐growing aquaculture industry, aquafeed production in China increased from 5.1 mmt in 2000 to 19.0 mmt in 2014, an increment of 272.5%. However, despite the rapid increase in aquafeed production, the fishmeal usage in aquafeeds in China has remained stable over the years. Fishmeal imports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(81 citation statements)
references
References 58 publications
(85 reference statements)
0
70
0
4
Order By: Relevance
“…The inclusion level of fishmeal is decreased year by year for all the species mentioned in Figure except catfish and was increased from 5% in 1995 to 11% in 2005, while the reduction was found in 2010 (5%). But in contrast, Han et al () reported an increased value of fishmeal inclusion in Yellow catfish (25%), Eels (55%) and shrimp (27%) for the year of 2014. The decreased availability and higher demand of fishmeal make a shift in the nutrient composition of aquafeeds in recent times for cost‐effective aquaculture production.…”
Section: Fish‐in/fish‐out Ratiomentioning
confidence: 90%
See 1 more Smart Citation
“…The inclusion level of fishmeal is decreased year by year for all the species mentioned in Figure except catfish and was increased from 5% in 1995 to 11% in 2005, while the reduction was found in 2010 (5%). But in contrast, Han et al () reported an increased value of fishmeal inclusion in Yellow catfish (25%), Eels (55%) and shrimp (27%) for the year of 2014. The decreased availability and higher demand of fishmeal make a shift in the nutrient composition of aquafeeds in recent times for cost‐effective aquaculture production.…”
Section: Fish‐in/fish‐out Ratiomentioning
confidence: 90%
“…Notwithstanding, feed technology is also one of the important factors, influencing fishmeal usage in aquafeed. Han et al () stated that the output of the recent research in the past few decades, not only increase the knowledge on digestibility and nutritional requirements of the candidate species and also gave a clear vision on the processing technology, which has led to a significant reduction in the usage of fishmeal in aquafeed formulation. FAO () reported that as the contribution of capture fisheries is relatively stable, the inclusion of fishery by‐products to global fishmeal supply is increased but this could affect the nutritional value of final products.…”
Section: Inevitability Of Fishmeal Replacement In Aquafeedsmentioning
confidence: 99%
“…Freshwater aquaculture in China has been viewed as one of the two main contributions of the nation to world aquaculture in the modern era (Han et al. ). Overall, pond aquaculture is likely to dominate aquatic food production; the pond freshwater culture area was 2.76 × 10 6 ha in 2016 (accounting for 44.71% of freshwater culture area), and pond culture production increased from 1.74 million metric tons in the early 1990s to 22.86 million metric tons in 2016 (Wang et al.…”
mentioning
confidence: 99%
“…We also emphasize that these perceptions are not time-bound characteristics of a certain culture or society, and we do not intend to imply that the Chinese market cannot be concerned with environmental sustainability at all. Chinese consumer preferences for lower-trophic level freshwater fish such as carp, for example, is a perception that arguably has more positive effects for the sustainability of fisheries (Han et al, 2016b). We also note that while we did not directly interview consumers themselves in this study, our assertions about consumer preferences are based not only on responses from traders but also earlier research conducted with consumers and restaurant operators (Fabinyi and Liu, 2014;.…”
Section: Discussionmentioning
confidence: 94%